2020
DOI: 10.1101/2020.08.24.20179457
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of the risk of SARS-CoV-2 reinfection in an intense re-exposure setting

Abstract: Background: Reinfection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been a subject of debate. We aimed to assess the risk and incidence rate of documented SARS-CoV-2 reinfection in a large cohort of laboratory-confirmed cases in Qatar. Methods: All SARS-CoV-2 laboratory-confirmed cases with at least one PCR positive swab that is ≥45 days after a first positive swab were individually investigated for evidence of reinfection, and classified as showing strong, good, some, or weak/no evid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
140
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(153 citation statements)
references
References 19 publications
9
140
1
3
Order By: Relevance
“…This is in agreement with the diagnosis (detection) rate estimated here at 12.1% (95% CI: 12.0-12.1%), as well as growing evidence from other countries indicating that only one in every 10 infections was ever diagnosed [24,[30][31][32][33]. The totality of evidence on the Qatar epidemic also indicates that most infections were asymptomatic or minimally mild to be diagnosed [5][6][7][8][9][34][35][36]. For instance, a national SARS-CoV-2 PCR survey found that 58.5% of those testing PCR positive reported no symptoms within the preceding two weeks of the survey [5].…”
Section: Discussionsupporting
confidence: 87%
“…This is in agreement with the diagnosis (detection) rate estimated here at 12.1% (95% CI: 12.0-12.1%), as well as growing evidence from other countries indicating that only one in every 10 infections was ever diagnosed [24,[30][31][32][33]. The totality of evidence on the Qatar epidemic also indicates that most infections were asymptomatic or minimally mild to be diagnosed [5][6][7][8][9][34][35][36]. For instance, a national SARS-CoV-2 PCR survey found that 58.5% of those testing PCR positive reported no symptoms within the preceding two weeks of the survey [5].…”
Section: Discussionsupporting
confidence: 87%
“…For staff members, the presence of IgG most likely means they are unlikely to get reinfected in the next months and spread the virus. While it has been demonstrated using full-length genome sequencing that individuals can be reinfected [17,18], a recent study in Qatar where an estimated 50% of the population had been infected with SARS-CoV-2 suggests the rate of reinfection in an intense re-exposure setting is very low (less than 0.1% suspected reinfections 1.5 to 4 months after the first infection) [19]. From an epidemiological perspective, staffing nursing homes with staff who tested positive for IgG could help bring down the high case-fatality rates [20].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, re-infection with other coronaviruses can occur with stable and high antibody titres. In a study where 133,266 laboratory-confirmed cases were evaluated with 243 positive swabs after 45 days of their first SARS-CoV-2 infection, it was found that 54 of these cases had re-infection considering their Ct values or symptoms of COVID-19 [ 71 ]. However, these cases cannot be determined to be true re-infection because neither WGS nor viral culture was used to identify these cases.…”
Section: Criteria For Sars-cov-2 Reinfection Diagnosismentioning
confidence: 99%
“…However, these cases cannot be determined to be true re-infection because neither WGS nor viral culture was used to identify these cases. Yet, the risk and incidence of re-infection was estimated to be 0.04% (95% CI: 0.03%–0.05%) and 1.09 (95% CI: 0.84–1.42) per 10,000 persons respectively [ 71 ].…”
Section: Criteria For Sars-cov-2 Reinfection Diagnosismentioning
confidence: 99%